Effect of ontogenic age on root and shoot development of Tabebuia heterophylla cuttings propagated in soilless culture - Awang, Yahya; Sandrang, Ab Kahar; Mohamad, Rosli; Selamat, Ahmad (Academic Journals, 2011)
A study was conducted to evaluate the root and shoot development in cuttings of Tabebuia heterophyllataken from varying ages of stock plants (1, 6, 18, 36 and 60 months). Cuttings obtained from the mother plants were rooted on perlite in saturated propagation chambers for 60 days. Generations of new roots and their subsequent growth, and the growth of new leaves from the cutting were reduced exponentially as the age of the stock plants increases, following a decay curve of y=Ae-bx.. In contrast, accumulation of leaf dry weight was highest in cuttings taken from six months old stock plants as explained by a modified Hoerl function of y=A*b(1/x)*x-c. The ability of juvenile cuttings to form roots was easier compared with older cuttings, and hence produces a larger root ball, these cuttings are expected to have a higher ability to survive.